Calidad bacteriológica de las aguas subterráneas de consumo humano en el centro poblado de Virú, distrito Virú, Perú, 2018 - Gutierrez Araujo, Mayra Karina (2019)
ABSTRACT Of the total number of existing wells in the Virú district, only 1139 are wells used; of which 1,022 wells (89.73%) are open pit and 117 tubular (10.27%). Knowing the bacteriological quality of the subterranean water of the district of Virú, the absence of pathogenic microorganisms that could cause serious diseases to the population is assured, that is why the objective of this research work was to determine if the groundwater consumed by the inhabitants of the Viru district is apt bacteriologically, as well as to evaluate the possible parameters that influence its contamination and inform the authorities of the necessary measures to reduce or eliminate the sources of contamination, because it is an important factor in the prevention of diseases. 32 tubular and open-pit wells were sampled, located in the El Frontón, Californias, Los Pinos, Huancaco, La Gloria, Huancaquito alto, El Carmelo and Santa Elena sectors, in the district of Virú, La Libertad during the months of July and November of the year 2018. The mentioned wells are of importance because they distribute water for human consumption for a large number of families of the Virú district for which 32 wells (20 tubular wells and 12 open pit wells) were evaluated, using the technique of multiples of Most Probable Number (NMP), the presence of total coliforms in 100% of thermotolerant wells and coliforms was determined in 25% of them; and to determine heterotrophic bacteria, the "plate count" technique was used, where most of them exceeded the limits suitable for human consumption. The groundwater of the tubular wells and open cutoff of the district of Virú, are not suitable for human consumption, being used only for agriculture and recreational activities prior to chlorination.